Stories of Place Geographies of Meaning, Memory and Connection - Kothari, Uma.; Borovnik, Maria; Everingham, Phoebe; Henrique, Karen Paiva; Miller, Fiona; Osborne, Natalie; Palis, Joseph; Wright, Sarah; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2026)
This book explores the role and agency of stories and storytelling in understanding places and in revealing how places tell stories. It addresses themes of colonialism, more-than-human agency, environment, atmospheres, borders, dwelling, enchantment, haunting, care and hope, revealing the power of stories to make and unmake worlds. Contending with the ethical complexities of storytelling and the political implications of the stories that are shared and heard, it illuminates how some stories dominate ways of being and knowing while others are excluded and overlooked. Ultimately, this book demonstrates how stories can provide alternative, critical and progressive ways of knowing and encountering place. Uma Kothari Professor of Migration and Postcolonial Studies, Global Development Institute, University of Manchester, UK. Maria Borovnik Senior Lecturer in Development Studies, School of People, Environment and Planning, Massey University, Aotearoa New Zealand. Phoebe Everingham Lecturer in Environment and Society, Discipline of Geography and Planning, Macquarie University, Australia. Karen Paiva Henrique Assistant Professor, Department of Human Geography, Planning and International Development, University of Amsterdam, Netherlands. Fiona Miller Associate Professor of Geography and Planning, Macquarie University, Australia. Natalie Osborne Senior Lecturer in urban and environmental planning, School of Engineering and Built Environment, Griffith University, Australia. Joseph Palis Faculty, Department of Geography, University of the Philippines-Diliman, Philippines. Sarah Wright< Professor of Geography and Development Studies, University of Newcastle, Australia.
Chapter 1: Positioning: Stories of place Storying Geography Collective -- Chapter 2: Responding: Absence, loss and power -- Chapter 3: Imagining: Disrupting colonial imaginaries, creating postcolonial stories -- Chapter 4: Haunting: Storying lively death -- Chapter 5: Situating: Fading polaroids of place -- Chapter 6: Relating: Storying atmosphere of place -- Chapter 7: Journeying: Geographies of belonging in a fractured world -- Chapter 8: Dwelling: Domesticity, decay, and inhabiting otherwise -- Chapter 9: Enchanting: Homage to my mum and Sandhills Community garden -- Chapter 10: Inviting: An epilogue.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Human geography; Cultural geography; Environmental sciences -- Social aspects; Culture -- Study and teaching; Literature; Anthropology; Social and Cultural Geography; Environmental Social Sciences; Human Geography; Cultural Studies; Literary Methods; Anthropology